The Influence of Service-Learning on the Civic Attitudes and Skills of Japanese Teacher Education Candidates - Miyazaki, Takeshi; Anderson, Jeffrey B.; Jones, Stacey (International Journal of Research on Service-Learning in Teacher Education, 2018)
This study examined the effectiveness of integrating a service-learning project into the undergraduate curriculum for students majoring in education at an urban university in Japan. These teacher candidates engaged in service-learning by supporting high school students in the development and implementation of social action projects. The study employed pre and post seminar data from the Civic Attitudes and Skills Questionnaire (CASQ) and student reflection papers to examine the influence of service-learning participation on the civic attitudes and skills of the teacher candidates. Results indicate that while the teacher candidates experienced a variety of benefits from their participation in service-learning, including significant gains in their civic action and political awareness, their self- perception of leadership skills declined significantly. Discussion centers on differences in the understanding and application of personal skills, such as leadership, between the culture of Japan, where the study took place, and the culture of the United States, where the CASQ was developed. Cultural differences need to be taken into account in order to appropriately interpret the results of the CASQ leadership scale when applied in a Japanese setting.